A One Hundred-Year-Study of Climate Change and the Upper Range of Tree Growth (Terminus arboreus) on MT. Getryggen in the Swedish Scandes – Updated Change in an Historical Perspective - Leif Kullman; Lisa Öberg (Emerging Issues in Environment, Geography and Earth Science Vol. 9, 2024)
In the context of global climate change, positional treeline change since the early 20th century and up to 2023 was assessed along two elevational transects on Mt. Getryggen in the southern Swedish Scandes. Baseline data within permanent line transects, initially representing the year 1915, i.e. right at the onset of the present warming phase, were compared to later intermittent records up to 2023. These were complemented by repeat photography of individual trees. Concerned species were the regional treeline dominants; mountain birch (Betula pubescens ssp. czerepanovii), Norway spruce (Picea abies), Scots pine (Pinus sylvestris) and Grey alder (Alnus incana). Treelines of these species responded with different degrees of upshifts, although with substantial inter-site variability, related to topoclimatic conditions. Betula displayed the largest advance, by 215 m over the entire past 100 years. This maximum magnitude of change complies with data from widely different parts of the Swedish Scandes. Such a common performance indicates that regionally recorded summer and winter warming by 1.4 and 1.9°C, respectively, is the ultimate cause. In a long-term historical perspective, recorded by local megafossil tree remnants, most congenial conditions for birch and pine growth at high elevations prevailed around 10 500-9400 cal. yr BP, when the local treeline of Betula and Pinus reached 1355 and 1250 m a.s.l., respectively. The former elevation coincides with the upper limit of Vaccinium myrtillus and the upper range of the low-alpine belt. With the exception of Pinus, recent treeline upshifts were mainly accomplished by phenotypic responses of millennial-old krummholz specimens (environmentally dwarfed modes), prevailing as relicts above the treeline by the early 20th century. Only occasionally, has treeline advance by Betula and Picea originated from seed regeneration during the past century. These circumstances may set the limit for further rapid and extensive advance of the last-mentioned species, where and when the pool of high-altitude old-established krummholz specimens becomes depleted. The prospect of further advance of seed disseminated Pinus, is judged to be higher, according to recent trends.